Elements of chemical reaction engineering - Fogler, H. Scott (Upper Saddle River, NJ : Prentice Hall PTR, 2006)
'Elements of Chemical Reaction Engineering', fourth edition, presents the fundamentals of chemical reaction engineering in a clear and concise manner.
The Definitive, Fully-Updated Guide to Solving Real-World Chemical Reaction Engineering Problems. This book combines authoritative coverage of the principles of chemical reaction engineering with an unsurpassed focus on critical thinking and creative problem solving. Clear, concise, and superbly organized, it integrates text, visuals, and computer simulations to help readers solve even the most challenging problems through reasoning, rather than by memorizing equations. H. Scott Fogler has thoroughly updated his classic text to provide even more coverage of industrial chemistry with real reactors and reactions, and an even broader range of applications. This edition's examples range far and wide, from smog to digestion, antifreeze to cobra bites, and computer chip manufacturing to chemical plant safety. Coverage includes Fundamental concepts: mole balances, conversion, reactor sizing, rate laws, and stoichiometry. Collection and analysis of rate data: equal-area differentiation, polynomial fitting, numerical difference formulas, regression, half lives, and more Reaction mechanisms, pathways, bioreactions, and bioreactors. unsteady-state nonisothermal reactors. Catalysis and catalytic reactors: selectivity, yield, and multiple reaction algorithms. External diffusion effects on heterogeneous reactions: Fick's Law, mass transfer coefficients, region mass transfer limitation, and the shrinking core model. Diffusion and reaction in porous catalysts, including Thiele modules. Distributions of residence times for chemical reactors. Models for nonideal reactors: tanks-in-series, dispersion one parameter models, and Peclet numbers Sample problems drawn from the California Civil and Professional Engineers-Chemical Engineering Examination (PECEE)Extensive reference content: numerical techniques, ideal gas constant/conversion factors, thermodynamic relationships, slope measurement, molecular dynamics, nomenclature, and more. The CD-ROM contains more than fifty interactive computer simulation tutorials, plus summary notes, additional examples, expanded derivations, mathematics software, and advanced content - ranging from collision and transition state theory to aerosol reactors, DFT, and runaway reactions.
Mole balances -- Conversion and reactor sizing -- Rate laws -- Stoichiometry -- Isothermal reactor design. conversion -- Isothermal reactor design : moles and molar flow rates -- Collection and analysis of rate data -- Multiple reactions -- Reaction mechanisms, pathways, bioreactions, and bioreactors -- Catalysis and catalytic reactors -- Nonisothermal reactor design : the steady-state energy balance and adiabatic PFR applications -- Steady-state nonisothermal reactor design : flow reactors with heat exchange -- Unsteady-state nonisothermal reactor design -- Mass transfer limitations in reacting systems -- Diffusion and reaction -- Distributions of residence times for chemical reactors -- Predicting conversion directly from the residence time distribution -- Models for nonideal reactors.
Includes bibliographical references and index.
System requirements: Windows or Power MAC with PC emulator.
Keywords: Chemical reactors